1983
DOI: 10.1093/ajcn/37.6.961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbohydrate on plasma and erythrocyte glutamate levels in humans ingesting large doses of monosodium L-glutamate in water

Abstract: In previous studies, plasma glutamate concentration was lower when equivalent doses of monosodium L-glutamate (MSG) were given with a ready-to-feed liquid formula meal (Sustagen; 0.4 g protein, 1.1 g carbohydrate, 0.06 g fat, 6.6 kcal energy/kg body weight) rather than in water. This difference was suggested to reflect a carbohydrate effect on mucosal cell glutamate metabolism. To test this hypothesis, a large dose of monosodium L-glutamate (150 mg/kg body weight) dissolved in water, with or without added carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
33
4
2

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 29 publications
9
33
4
2
Order By: Relevance
“…When MSG (150 mg/kg bw) was given together with carbohydrate (1.1 g/kg bw in the form of hydrolyzed corn starch), time to reach the plasma glutamate peak and time to return to basal were similar to the values observed when glutamate was given alone [19]. However, the peak plasma concentration was lowered ( Table 2).…”
Section: Pharmacokinetics Of Dietary Glutamatesupporting
confidence: 54%
See 2 more Smart Citations
“…When MSG (150 mg/kg bw) was given together with carbohydrate (1.1 g/kg bw in the form of hydrolyzed corn starch), time to reach the plasma glutamate peak and time to return to basal were similar to the values observed when glutamate was given alone [19]. However, the peak plasma concentration was lowered ( Table 2).…”
Section: Pharmacokinetics Of Dietary Glutamatesupporting
confidence: 54%
“…There was no change in glutamate levels in red blood cells [19]. Some years later, Graham et al [24] conducted a similar study and obtained closely similar results.…”
Section: Pharmacokinetics Of Dietary Glutamatementioning
confidence: 66%
See 1 more Smart Citation
“…However, since the carbohydrate content of the food administered with glutamate varied between groups (formula for infants and porridge for adults), the plasma glutamate levels are not directly comparable. Further, the plasma glutamate levels observed by Tung and Tung (20) in infants and adults were significantly lower than values we observed in normal adults administered 150 mg/kg body weight of MSG in water, where peak plasma glutamate levels reached 59.4 k 46.5 pmol/dl (16). Thus, the data of Tung and Tung (20) may be explained by the effect of carbohydrate on glutamate metabolism.…”
Section: Discussioncontrasting
confidence: 60%
“…In the present study, amino acid concentrations were measured in blood plasma but not in erythrocytes. However, it was previously shown that erythrocyte glutamate and aspartate concentrations were not affected in humans after administration of large doses of MSG [31]. Although dicarboxylic amino acids are highly concentrated in red blood cells, it is generally considered that the exchanges with plasma proceed very slowly, and thus this intracellular pool contributes poorly to interorgan fluxes.…”
Section: Discussionmentioning
confidence: 99%